Teaching Media Law to Journalism Students: Different Needs, Different Strategies - Mark Pearson (Legal Education Review)
Almost all tertiary journalism courses offer media law components in their curricula. It is expected by both educators and the profession that all graduates should have an understanding of pertinent areas of the law, including defamation, confidentiality, contempt and privacy. However, courses vary in the quantity of legal education in their curricula and in their pedagogical approaches. For example, while some courses cover a bare minimum, others endeavour to give students a considerable understanding of legal research methods and an advanced knowledge of the legal system. Some extend the curriculum to cover areas of the law which might only be of peripheral interest to journalists (for example, contract and Trade Practices legislation) and explore ways journalists might use the law to enhance their reporting (such as the use of Freedom of Information legislation or corporations law). This paper considers the issue of media law education for journalism students in tertiary institutions and suggests journalism students require a different legal curriculum and pedagogy from that offered to law students. Its purpose is to question the foundations of legal instruction to journalism students and to foreshadow an alternative approach which better develops legal competences for the journalism enterprise. Media law is usually taught by either lawyers based in law faculties, former journalists with legal qualifications who visit as guest or part-time instructors, or by journalism staff who have some legal interest or qualification. Media law texts and readings usually emanate from a strictly legal source (for example, Sally Walker’s Law of Journalism in Australia). When it is taught by lawyers or journalism staff with a legal background it is often approached as if it were another law subject for law students, with professors becoming disenchanted with journalism students’ lack of familiarity with the “legal way of thinking” and their ignorance of the legal system and its operations. The temptation is to cover complex legal concepts all too quickly sometimes in a single semester, as if the students could get their “quick fix” in media law and thus be equipped with the skills and understandings necessary to deal with legal issues as working journalists. Students might leave with some knowledge of pitfalls in the law for journalists but little understanding of how to deal with them. Take, for example, the complex area of defamation law and assume the course allows a single media law subject in the degree. Defamation is such an important area of the law affecting journalists that it would be reasonable to expect an instructor to allocate it a substantial portion of the subject. The law professor is then faced with the daunting task of condensing into a few weeks content which might take a full two torts subjects in a law degree — and teaching it to students who may not have been instructed in the workings of the legal system, legal methods of research or case appraisal and citation. The professor might well choose to give a potted version of the larger course, perhaps selecting the key concepts and addressing a major case to illustrate each. However, the instructor could hardly state confidently that the students have left the course with a deep enough understanding of media law to be able to deal with actual scenarios in the news room.